The Gambia : Second Review Under the Extended Credit Facility Arrangement-Press Release; and Staff Report. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2021)
The Gambia is experiencing a second wave of COVID-19 cases. The vaccination campaign started in early March 2021, but the pace is slow, due to vaccine availability and hesitancy. Presidential and parliamentary elections are planned for December 2021 and April 2022, respectively.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements; International Organizations; Monetary Policy; Observance; Gambia, The